Comparison of a Recombinant-antigen Enzyme Immunoassay with Treponema pallidum Hemagglutination Test for Serological Confirmation of Syphilis - Islay Rodríguez; Elvio L Álvarez; Carmen Fernández; Alina Miranda (Memorias do Instituto Oswaldo Cruz, 2002)
A recombinant-antigen enzyme immunoassay (EIA), BioSCREEN TM anti-Treponema pallidum, was compared favorably with the T. pallidum hemagglutination test, in the detection of specific antibodies in different groups of sera from patients with primary (n = 38), secondary (n = 10), early latent (n = 28) and congenital syphilis (n = 2), patients with leptospirosis ( n= 8), infectious mononucleosis (n = 7), hepatitis (n = 9), diabetes mellitus (n = 11), rheumatoid arthritis (n = 13), leprosy (n = 11), tuberculosis (n = 9), HIV/Aids ( n= 12), systemic lupus erythematosus (n = 4), rheumatic fever (n = 3), old-persons (n = 9), pregnant women (n = 29) and blood donors (n = 164). The coincidence between them was 95.1%. The sensitivity and specificity of the EIA were 93.3% and 95.5%, respectively. Fifteen serum specimens belonging to old-persons, pregnant women, blood donors, and patients with human leptospirosis, hepatitis, diabetes mellitus, tuberculosis and rheumatic fever gave false-positive results by Venereal Disease Research Laboratory and/or Rapid Plasma Reagin. The EIA can be used as alternative method for the serological confirmation of syphilis.